SMOC2 gene interacts with APOL1 in the development of end-stage kidney disease: A genome-wide association study - Chaudhary, Ninad S.; Armstrong, Nicole D.; Hidalgo, Bertha A.; Gutiérrez, Orlando M.; Hellwege, Jacklyn N.; Limdi, Nita A.; Reynolds, Richard J.; Judd, Suzanne E.; Nadkarni, Girish N.; Lange, Leslie; Winkler, Cheryl A.; Kopp, Jeffrey B.; et al. (Frontiers in Medicine, 2022)
Background: Some but not all African-Americans who carry APOL1 nephropathy risk variants (APOL1) develop kidney failure (ESKD). To identify genetic modiifers,we assessed gene-gene interactions in a large prospective cohort of the REasons for Geographic and Racial Differences in Stroke (REGARDs) study. Methods: Genotypes from 8,074 African-americans participants were obtained from llumina Infinium Multi-Ethnic AMR/AFR Extended BeadChip. We compared 388 incident ESKD cases with 7,686 non-ESKD controls, using a two-locus interaction approach. Logistic regression was used to examine the effect of APOL1 risk status (using recessive and additive models), SNP, and APOL1*SNP interaction on incident ESKD, adjusting for age, sex, and ancestry. APOL1*SNP interactions that met the threshold of 1.0 X10-5 were replicated in the Genetics of Hypertension Associated Treatment study (626 ESKD cases and 6,165 controls). In a sensitivity analysis, models were additionally adjusted for diabetes status. We conducted additional replication in the BioVU study. Results: Two APOL1 risk alleles prevalence (recessive model) was similar in the REGARDs and GenHAT studies. Only one APOL1-SNP interaction, for rs7067944 on chromosome 10, ~10KB from PCAT5 gene met the genome-wide statistical threshold (P interaction = 3.4 X 10-8), but this interaction was not replicated in the GenHAT study. Among other relevant top findings (with Pinteraction<1.0 X 10-5), a variant (rs2181251) near SMOC2 on chromosome 6 interacted with APOL1 risk status (additive) on ESKD outcomes (REGARDS study, P interaction =5.3 x10-6, GenHAT study, P interaction =0.07). The association with the locus near SMOC2 persisted in further sensitivity analyses. Among those who inherited ≥ 1 alternate allele of rs2181251, APOL1 was associated with an increased risk of incident ESKD (OR [95%CI] = 2.27[1.53, 3.37]) but APOL1 was not associated with ESKD in the absence of the alternate allele (OR [95%CI] = 1.34[0.96, 1.85]). The associations were consistent after adjusting for diabetes. Conclusion: In a large Genome Wide Association study of African-Americans, a locus SMOC2 exhibited a significant interaction with the APOL1 locus. SMOC2 contributes to progression of fibrosis after kidney injury and the interaction with APOL1 variants may contribute to an explanation for why only some APOLI high-risk individuals develop ESKD.